The Intonation of the Left Periphery: A Matter of Pragmatics or Syntax?. (16th July 2019) - Sequeros‐Valle, Jose
Abstract: This article investigates the intonation of the left periphery and its relationship with discourse and syntax. While some authors hypothesize that intonational patterns align with discourse functions (Bianchi & Frascarelli 2010, Frascarelli & Hinterhölzl 2007), others argue that intonational patterns are correlated with different types of constructions (Feldhausen 2016). In order to solve whether discourse or syntax predicts intonation in the left periphery, 12 participants completed a scripted production task. Two syntactic constructions, focus fronting and clitic‐doubled left dislocation, and two discourse functions, contrast and familiarity, were combined into three conditions: (i) contrastive–focus fronting, (ii) contrastive–clitic‐doubled left dislocation, and (iii) familiar–clitic‐doubled left dislocation. Results show that the overall intonational pattern of the left periphery aligns to construction type, with focus fronting presenting one nuclear configuration (L+H* L‐ no‐pause) and clitic‐doubled left dislocation presenting a different one (L+H* !H no‐pause). These findings are consistent with the construction‐based hypothesis and challenge the discourse‐based hypothesis.